Distribution of the Mediterranean ribbed limpet Patella ferruginea Gmelin, 1791 along the Ligurian coast and implications for conservation actions - MARIA PAOLA FERRANTI; DAVIDE MONTEGGIA; VALENTINA ASNAGHI; ALESSANDRO DAGNINO; FEDERICO GAINO; PAOLO MORETTO; VERONICA PARODI; LUCA TIXI; VALENTINA CAPPANERA; CLAUDIO VALERANI; SIMONE BAVA; MARIACHIARA CHIANTORE (Mediterranean Marine Science, 2019)
Patella ferruginea is an endemic limpet of the Western Mediterranean Sea, presently considered the most threatened marine macroinvertebrate in the region and included in several international conservation directives. Its populations were widespread throughout the Western Mediterranean in the late Pleistocene (Tyrrhenian period), still largely distributed until the 19th century and presently confined into small populations in few restricted areas due to human harvesting for food and baits, construction of coastal infrastructures and the effects of seawater pollution. In particular, the species was reported as presently missing in the whole of the Italian continental coasts and measures are in progress to reintroduce the species through translocation and reproduction in controlled conditions along the Ligurian coasts (North-western Mediterranean).Recent surveys along the Ligurian coasts, performed to assess the most suitable sites for reintroduction, allowed the discovery of 32 specimens of this endemic limpet, considered disappeared in the area. These findings shed new light on the ability of natural dispersion of the species, the relevance of the measures set in place to restore the presently rarefied populations and provide hints for the selection and management of sites within the Natura 2000 Ecological network.